Vulvar dermatoses: a cross-sectional 5-year study. Experience in a specialized vulvar unit - Fernando García-Souto; Ana Isabel Lorente-Lavirgen; Francisco Manuel Ildefonso Mendonça; Manuel García-; Mariana Viktoria Hoffner-Zuchelli; Desiree Rodriguez-Ojeda; Elena Pozo; José Bernabéu-Wittel (Sociedade Brasileira de Dermatologia, 2022)
Abstract Background: Vulvar diseases are common in the general population and have a negative impact on the quality of life. Objectives: To describe our experience as dermatologists in the management of vulvar dermatosis consultations. Methods: A retrospective observational study was conducted with patients who attended monographic vulvar consultations over a 5-year period. Clinical information was obtained from the patient's charts. Results: 148 women were studied. Their mean age was 43.24 years (standard deviation: 15.15 years), with ages ranging from 4 months to 80 years. 53.4% of patients took between 2 and 5 years to seek medical attention for the first time. The most frequent diagnosis was lichen sclerosus (41.9%), irritative eczema of the vulva (14.9%), and lichen simplex chronicus (10.1%). 83.8% reported anogenital itching, 66.2% pain, and 45.9% dyspareunia. The most frequently prescribed treatment was ultra-potent topical corticosteroids (clobetasol propionate; 41.2%). Patients with lichen sclerosus were significantly older than those who presented with any of the other diseases. No differences were found in terms of either the time of disease evolution or in symptom presentation. Study limitations: Retrospective study. Vulvar diseases with an infectious cause are usually managed in primary care, therefore, were not included. All patients were recruited from a single private hospital which limits the comparisons with the public health system. Conclusions: Vulvar diseases frequently occur and are associated with high morbidity. It is essential to promote the development of specific vulvar consultations in hospitals. Specialties such as dermatology, gynecology, urology, or physiotherapy must be part of these units.